PROSES REKONSTRUKSI DALAM PELAKSANAAN PENYIDIKAN GUNA MENGUNGKAP KASUS TINDAK PIDANA PEMBUNUHAN BERENCANA DI KOTA MAKASSAR - Muhammad Elis Winandar; Hambali Thalib; Muhammad Rinaldy Bima (Qawanin Jurnal Ilmu Hukum, 2020)
This study aims to determine the implementation of investigations to uncover cases the crime of premeditated murder in the city of Makassar and knowing the reconstruction process of premeditated murder in the city of Makassar. The research method used in the writing of this thesis is an empirical method, with secondary and primary data coverage, this research was conducted at the Makassar Polrestabes. The results of this study indicate that the implementation of the investigation and the reconstruction process is very helpful in uncovering the crime case premeditated murder in the city of Makassar. The obstacle experienced by Makassar police investigators is the process of reconstructing a case of premeditated murder which resulted in the death of UMI (Muslim Indonesia University) student, namely Andi Predy Akrimas alias Andi lolo, the reconstruction process was not carried out at the crime scene (TKP) due to security factors, many community so that the reconstruction process was not carried out at the scene of the case. Research recommendations. All forms of constraints experienced by investigators, the authors expect the public to know the importance of carrying out the investigation and reconstruction process so that the community does not take actions that interfere with the investigation and reconstruction process.